2020
DOI: 10.1007/s12072-020-10034-0
|View full text |Cite
|
Sign up to set email alerts
|

Advanced liver disease outcomes after hepatitis C eradication by human immunodeficiency virus infection in PITER cohort

Abstract: Background Liver disease progression after Hepatitis C Virus (HCV) eradication following direct-acting antiviral (DAA) treatment in the real-life setting according to Human Immunodeficiency Virus (HIV) coinfection was evaluated. Methods Patients consecutively enrolled in PITER between April 2014 and June 2019 and with at least 12-weeks follow-up following treatment were analysed. Cox regression analysis were used to evaluate HIV coinfection and factors independently associated with liver disease outcomes follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 28 publications
4
8
0
2
Order By: Relevance
“…Regarding the HCC occurrence, a similar cumulative HCC incidence in coinfected (2.2%) and monoinfected (3.9%) (p=0.38) patients after viral eradication, was reported in our recent study, suggesting that HIV coinfection is not associated with a higher probability of developing liver complications in successfully DAA treated patients with compensated cirrhosis [3].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Regarding the HCC occurrence, a similar cumulative HCC incidence in coinfected (2.2%) and monoinfected (3.9%) (p=0.38) patients after viral eradication, was reported in our recent study, suggesting that HIV coinfection is not associated with a higher probability of developing liver complications in successfully DAA treated patients with compensated cirrhosis [3].…”
Section: Discussionsupporting
confidence: 87%
“…Sustained virologic response (SVR) reduces the risk of liver decompensation and of hepatocellular carcinoma (HCC) and improves survival [ 1 , 4 , 5 ]. However, a “point of non-return” in terms of deterioration of liver function, has been observed in part of patients regardless of viral eradication, potentially due to the pre-treatment severe liver fibrosis and/or presence of other cofactors of liver disease progression [ 3 , 4 , 6 ]. As a cofactor, Human Immunodeficiency Virus (HIV) coinfection negatively affect the natural course of chronic HCV infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the overall SVR12 rate (93.9% and 94.1% in coinfected and monoinfected patients, respectively) is similar to those reported in clinical trials and in our previous study (18), con rming the high e cacy of DAA therapy in the real-world setting also in patients with advanced liver disease, regardless of HIV coinfection (18)(19)(20)(21). The results of this medium-term study con rm that HCV clearance obtained by DAA is feasibly linked to an improved outcome in patients with advanced liver disease, independently by HIV-coinfection.…”
Section: Discussionsupporting
confidence: 90%
“…In individuals with compensated cirrhosis, HIV coinfection was not related with an increased probability of liver complications after viral eradication than those HCV-monoinfected[ 93 , 94 ]. In the series of Corma-Gómez et al [ 95 ], the likelihood of staying free of hepatic complications or transplant at 12 and 24 mo was 99% and 96% in HCV-monoinfected patients and 99 and 98% in HIV/HCV coinfected patients with predominantly (> 95% of individuals) Child-Pugh class A cirrhosis ( P = 0.648).…”
Section: Effects Of Svrmentioning
confidence: 99%